Targeting the 8-oxodG Base Excision Repair Pathway for Cancer Therapy - Anna Piscone; Francesca Gorini; Susanna Ambrosio; Anna Noviello; Giovanni Scala; Barbara Majello; Stefano Amente (Cells)
Genomic integrity is critical for cellular homeostasis, preventing the accumulation of mutations that can drive diseases such as cancer. Among the mechanisms safeguarding genomic stability, the Base Excision Repair (BER) pathway plays a pivotal role in counteracting oxidative DNA damage caused by reactive oxygen species. Central to this pathway are enzymes like 8-oxoguanine glycosylase 1 (OGG1), which recognize and excise 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG) lesions, thereby initiating a series of repair processes that restore DNA integrity. BER inhibitors have recently been identified as a promising approach in cancer therapy, increasing the sensitivity of cancer cells to radiotherapy and chemotherapy. By exploiting tumor-specific DNA repair dependencies and synthetic lethal interactions, these inhibitors could be used to selectively target cancer cells while sparing normal cells. This review provides a robust reference for scientific researchers, offering an updated perspective on small-molecule inhibitors targeting the 8-oxodG-BER pathway and highlighting their potential role in expanding cancer treatment strategies.